Determining effective faults for hydrocarbon accumulation in slope areas of petroliferous basins: Methods and applications - Zili, Fan; Guang, Fu; Xiaodong, Fan; Shuli, Wang; Hongwei, Xiao; Hongjun, Fu; Xiaobo, Guo (Frontiers in Earth Science, 2023)
From accumulation mechanisms and the identification of effective faults, hydrocarbon distribution in slope areas of petroliferous basins is assessed. In this study, we superimpose two methods to develop a set of key methods, which could identify effective faults for hydrocarbon accumulation in slope areas. The first of this set of methods includes: by locating the distribution area of the connected sand bodies and paleotectonic ridges overlying the formation where the sand bodies are located, determining the lateral migration path of hydrocarbons in slope areas. The second set of methods includes: by identifying the lateral sealing parts of faults that are oriented perpendicular or oblique to the channel sand bodies, determining the effective faults. By applying these methods, identifying effective faults in the 1st member of the Nantun Formation (K1n1) on the Wunan slope of the Wuerxun Depression in the Hailar Basin. The results show that the effective faults in K1n1 are located mainly in its middle and northern parts, with a few distributed in the south-central part. This is conducive to reservoir development, since hydrocarbons, which generated in the western trough source rocks of K1n1, accumulated in the nearby trap formed from a suitable configuration of the fault and sand body of K1n1. This is consistent with previous exploration data, and that is hydrocarbons discovered in K1n1 on the Wunan slope are mainly distributed in the middle and northern parts of the region, and a small amount occur in the south-central part. The results show that this set of methods is feasible for determining effective faults for hydrocarbon accumulation in slope areas.